Entrepreneurship Education as a Solution for Developing Entrepreneurial Character and Ability in Indonesia - Farihatul Hasanah (CV. ITTC INDONESIA, 2024)
This entrepreneurship education is given to students as early as possible considering the economic problems faced in Indonesia. Entrepreneurship education is basically a process of internalizing Entrepreneurship values to students so that they have a character like an entrepreneur. The value of entrepreneurship is important for students to have to face life problems, the purpose of this study is to find out the goals and characteristics of entrepreneurship education. The research method used is library research with a descriptive approach. Data analysis techniques use data reduction, data presentation and conclusions. The results of this study state that entrepreneurship education aims to develop attitudes, spirits and the ability to create something valuable for oneself and others. There are five main values in Entrepreneurship education, including the courage to take risks, be creative in facing problems and opportunities, have a leadership spirit, be task- and result-oriented, and have strong motivation and drive to succeed.